Assessing adherence to direct oral anticoagulants (DOACs) among patients with atrial fibrillation in tertiary-care referral centers in Malaysia - Kubas, Mohammed Abdullah; Shabaruddin, Fatiha Hana; Mazlan-Kepli, Wardati; Jagan, Nirmala; Mohamed, Sahimi; Mohamed Nazar, Nor Ilyani; Zin, Che Suraya (2019)
INTRODUCTION Direct oral anticoagulants (DOACs), such as dabigatran and rivaroxaban, are now available for stroke prevention in patients with atrial fibrillation (AF) and are often clinically preferred over vitamin K antagonists (VKAs), such as warfarin. Data describing adherence to DOACs in real-life clinical practice in Malaysia are scarce. OBJECTIVES This study aimed to assess adherence to DOACs in patients with AF at Hospital Kuala Lumpur (HKL) and Hospital Serdang (HSDG), tertiary-care referral centers. METHODOLOGY This was a retrospective cohort study that included all AF patients who were treated with DOACs (dabigatran or rivaroxaban) in HKL and HSDG. Data were obtained from medical records and pharmacy database. Adherence was assessed by using proportion of days covered (PDC) over a 1-year duration and was calculated as the number of days that the medication was on hand over the total number of days in the time period. Good adherence was defined as PDC ≥80% RESULTS There were 281 patients who met the inclusion criteria, male 54.1% (n=152), with 75.1% (n=211) patients on dabigatran and others on rivaroxaban. The ethnic distribution was Chinese 49.8% (n=140), Malay 41.6% (n=117), and Indian 8.5% (n=24). Only 66.9% of patients achieved good adherence with PDC ≥ 80%. Adherence by institution was good in HKL with 85.2% (n=69/81) but poor in HSDG with 59.5% (n=119/200) [p<0.05]. CONCLUSION Overall adherence to DOACs was poor but it varied between institutions, potentially due to institution-specific administrative and clinical practice differences. Clinical care can potentially be optimized by identifying factors affecting adherence and implementing adherence-improving interventions.